Exploring the mechanism of live streaming e-commerce anchors’ language appeals on users’ purchase intention - Ma, Erwei; Liu, Jiaojiao; Li, Kai (Frontiers in Psychology, 2023)
Introduction Live streaming e-commerce is an important way for consumers to shop nowadays. Anchors, as salesperson in live streaming e-commerce, greatly affect the sales of the broadcast room. This paper studies the influence mechanism of anchors’ language appeals, rational appeal, and emotional appeal on users’ purchase intention. This study establishes a research framework which based on stimulus-organism-response (SOR) theory, and constructs a model to reflect the relationship between anchors language appeals, self-referencing, self-brand congruity, and purchase intention. Methods Survey using a convenience sample (N = 509) was conducted on Chinese mainland netizens through WJX platform (October 17-23, 2022) to obtain data. The partial least square structural equation modeling (PLS-SEM) method was used for data analysis. Results The study found that anchors’ language appeals was positively correlated with self-referencing and self-brand congruity, and there is a positive correlation between self-referencing, self-brand congruity, and purchase intention. Self-referencing and self-brand congruity play a mediating effect between anchors language appeals and purchase intention. Discussion This study advances the literature on live streaming e-commerce research and SOR and provides practical implications to influence the strategy of the e-commerce anchors.